Philosophische Übersetzung zwischen "sprachlicher Gewaltanwendung" und translativer Hermeneutik. Translatorische Überlegungen aus der Sicht der Übersetzung(en) von Jean-Paul Sartres 'L'être et le néant' - Yvanka Raynova (Labyrinth: An International Journal for Philosophy, Value Theory and Sociocultural Hermeneutics, 2019)
Philosophical translation between "linguistic violence" and translative hermeneutics. Translational considerations from the perspective of the translation(s) of Jean-Paul Sartre's L'être et le néant